Effect of Shear Reinforcement on the Structural Behaviour of the Reinforced Concrete Deep Beam - Sai Sri Vidyadhari, A; Sri Harsha, G (International Journal of Engineering and Technology, 2018)
The present study explains about the behavior of Deep beams in both experimental and analytical aspect. Considering the maximum moment from the analytical analysis, the Deep beams are designed according to the IS-456[2000] codal provisions. The failure of deep beams is mainly due to shear, which is considered as a catastrophic failure and many studies are being done on their behavior, some studies concluded that strut-tie- method(STM) is most relevant, but the IS-456(2000) code has no provisions regarding the STM. So, in the present study, the reinforcement area obtained in conventional design of deep beams as per IS provisions were arranged in the form of truss. Thus, comparing the behavior of conventional reinforced Deep beams with truss configured Deep beams, and comparing experimental results with analytical results of Deep Beams. The results concluded that the truss reinforced Deep beams shown good results compared to Conventional Deep Beams and IS-456 code need to be updated for the deep beam design in various approaches. Â Â